2005
DOI: 10.1021/ma048895d
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the CO2Antisolvent Effect on Ultrasound-Induced Polymer Scission Kinetics

Abstract: Ultrasound-induced polymer scission is a nonrandom process which alters the molecular weight distribution of polymers. However, transient cavitation, and consequently polymer scission, is not possible in concentrated polymer solutions due to the high liquid viscosity. The addition of an antisolvent can be used to circumvent this problem because the antisolvent decreases the gyration radius of polymer chains, which induces a reduction in liquid viscosity. To determine the influence of carbon dioxide (CO2) as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…The predicted M lim values have experimentally been confirmed for each system studied. In this study a decrease in polydispersity is observed from 2.4 to 1.5 for all scission experiments, as described previously 29,30…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…The predicted M lim values have experimentally been confirmed for each system studied. In this study a decrease in polydispersity is observed from 2.4 to 1.5 for all scission experiments, as described previously 29,30…”
Section: Resultssupporting
confidence: 62%
“…From the slope of Figure 8, it can be seen that the scission rate is initially higher for the higher CO 2 fractions 0.08 and 0.14 as compared to the 0.02 fraction. This effect is explained in more detail in another paper 30. The negative influence of the CO 2 ‐fraction on the implosion velocity at low polymer concentrations (cushioning effect) is thus counteracted at higher polymer concentrations by the CO 2 anti‐solvent effect.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The ability of turbulent flow and shock waves produced by acoustic cavitation to drive metal particles together at very high velocities has been reported (Doktycz and Suslick, 1990). The increased bubble wall velocity at higher frequencies may also lead to a higher strain rate upon implosion of bubbles thus enhancing the shearing effect of cavitation (Kuijpers et al, 2005). In aqueous solutions, water vapor molecules and volatiles inside the cavities are thermolysed to generate highly reactive chemical species, such as hydroxyl, hydrogen and organic radicals (Ince et al, 2001;Han et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonic degradation of polymers depends on a variety of parameters, such as temperature, US intensity and frequency, concentration and initial molecular weight of the polymer 20–26. Price, Madras, Malhotra, Kuijpers and Desai have reported that polymer degradation parameters depend on the solvent properties 9, 20, 27–31. Most of the ultrasonic polymer degradation studies in the literature are performed by periodically removing samples from the reaction environment and measuring their molecular weights.…”
Section: Introductionmentioning
confidence: 99%